2002
DOI: 10.1046/j.0022-3042.2001.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐induced nitrative stress in the retina, and correction by aminoguanidine

Abstract: Aminoguanidine inhibits the development of retinopathy in diabetic animals, but the mechanism remains unclear. Inasmuch as aminoguanidine is a relatively selective inhibitor of the inducible isoform of nitric oxide synthase (iNOS), we have investigated the effects of hyperglycemia on the retinal nitric oxide (NO) pathway in the presence and absence of aminoguanidine. In vivo studies utilized retinas from experimentally diabetic rats treated or without aminoguanidine for 2 months, and in vitro studies used bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
180
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(204 citation statements)
references
References 44 publications
(70 reference statements)
21
180
3
Order By: Relevance
“…10) (El-Remessy, 2003a;Graier et al, 1999;Graier et al, 1997;Graier et al, 1996) resulting in peroxynitrite formation. Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 94%
See 1 more Smart Citation
“…10) (El-Remessy, 2003a;Graier et al, 1999;Graier et al, 1997;Graier et al, 1996) resulting in peroxynitrite formation. Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 94%
“…The mechanisms by which oxidative stress contributes to VEGF overexpression are not fully understood. However, inhibiting nitric oxide synthase (NOS) has been shown to prevent signs of diabetic retinopathy in rats (Du et al, 2002;El-Remessy, 2003b;Kowluru et al, 2000), suggesting that formation of reactive nitrogen species plays a role in the pathology. Recent studies also indicate a role for peroxynitrite in diabetic retinopathy.…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 99%
“…29 Another change that occurs in the early stages of diabetic retinopathy in animal models of diabetes is an upregulation of inducible NOS (iNOS). iNOS increases are seen in both glial cells and neurons in the retina 92,108 and result in increased NO levels. 108,109 As described above, NO, in addition to acting on vessels to induce vasodilation, is a modulator of neurovascular coupling that suppresses flicker-evoked vasodilation.…”
Section: Modulation Of Functional Hyperemia In the Retina Oxygen Modumentioning
confidence: 99%
“…Indeed, aminoguanidine has been shown to dramatically slow the progression of diabetic retinopathy in animal models of diabetes. [108][109][110][111][112] A human trial of aminoguanidine also demonstrates a slowing of diabetic retinopathy progression, although the trial was terminated early due to side effects of aminoguanidine when administered at high doses. 113 In addition to inhibiting iNOS, aminoguanidine also blocks formation of advanced glycation endproducts and its beneficial effect on diabetic retinopathy could be due to this effect on advanced glycation endproducts.…”
Section: Modulation Of Functional Hyperemia In the Retina Oxygen Modumentioning
confidence: 99%
“…92 Further corroborating the contribution of hypertension to retinal damage in diabetic SHR, we have demonstrated that anti-hypertensive treatment either with losartan (an AT1 receptor blocker, ARB) or with triple therapies (hydralazine, reserpine and hydrochlorothiazide) abolished these effects. 84 In the retina, a number of studies have shown that there is an increase in oxidative markers after the induction of DM, 67,[93][94][95] but the concomitance of diabetes and hypertension evoked earlier oxidative retinal damage characterized by an increase in nitrotyrosine and 8-OHdG in retinal tissue from short-term STZ-induced DM in SHRs. [96][97][98][99] These oxidative markers were the consequence of an increase in superoxide production and depletion of the gluthationereduced antioxidant system in the retinal tissue.…”
Section: Inflammation and Oxidative Stress As The Underlying Mechanismentioning
confidence: 99%